Occlusal Features and Caries Experience of Hong Kong Chinese Preschool Children: A Cross-Sectional Study - Zhang, Shinan (Int J Environ Res Public Health, 2017)
Objective: To study occlusal features and their relation to caries experience in Hong Kong Chinese preschool children. Methods: Seven kindergarten classes in Hong Kong were selected using a stratified random sampling method, and the 4- and 5-year-old Chinese kindergarten children were invited to join the survey. Two calibrated dentists performed the clinical examinations in the kindergartens. Occlusion features, including incisal overjet; canine and molar relationship; median diastema; and primate space as well as malocclusion features, including crossbite; anterior open bite; and scissor bite, were recorded. Caries experience was recorded with the dmft index. Results: A total of 538 children were invited to participate in the study, and finally 495 children were examined (92%). Approximately half (52%) had a normal incisor relationship. Most children had a class I canine relationship (left-79%; right-75%). Approximately two-thirds had a flush terminal plane (left-64%; right-65%). Most children (76%) had a maxillary primate space, and 47% had a mandibular primate space. The prevalence of median diastema, anterior crossbite, and unilateral posterior crossbite was 30%, 12% and 1%, respectively. No bilateral posterior crossbite or scissor bite was found. Approximately half (49%) had caries experience. The mean dmft score was 2.1. Gender and age were not associated with either the studied occlusal features or the mean dmft score (p > 0.05). Conclusion: Approximately half of the Hong Kong preschool children studied had a normal occlusion, and two-thirds of them had a flush terminal plane. About three-quarters of them had a maxillary primate space, and half of them had a mandibular primate space. Their occlusal traits were not associated with caries experience and prevalence.